Aerodynamic study of time-trial helmets in cycling racing using CFD analysis - Beaumont, F.; Taiar, R.; Polidori, G.; Trenchard, H.; Grappe, F. (Journal of Biomechanics, 2018)
The aerodynamic drag of three different time-trial cycling helmets was analyzed numerically for two different cyclist head positions. Computational Fluid Dynamics (CFD) methods were used to investigate the detailed airflow patterns around the cyclist for a constant velocity of 15?m/s without wind. The CFD simulations have focused on the aerodynamic drag effects in terms of wall shear stress maps and pressure coefficient distributions on the cyclist/helmet system. For a given head position, the helmet shape, by itself, obtained a weak effect on a cyclist`s aerodynamic performance (<1.5%). However, by varying head position, a cyclist significantly influences aerodynamic performance; the maximum difference between both positions being about 6.4%. CFD results have also shown that both helmet shape and head position significantly influence drag forces, pressure and wall shear stress distributions on the whole cyclist`s body due to the change in the near-wake behavior and in location of corresponding separation and attachment areas around the cyclist.